Phytochemical and pharmacological potential of Solanum nigrum: A concise review - Adil Jamal; Aisha Nawaz; Amina Arif; Muhammad Naveed Shahid (Acta Biologica Slovenica)
Medicinal plants have been a great source of folk medicines for humans for centuries worldwide. Solanaceae family is the most prominent family of plants, having a large group of more than 1400 species present in tropical and temperate regions worldwide, including Solanum nigrum. This edible medicinal herb exhibits a wide range of therapeutic potential, predominantly encompassing anti-tumour, antioxidative, hepato-protective, antimicrobial, immune-modulatory, neuroprotective and anti-inflammatory properties. Phytoconstituents and therapeutic properties of S. nigrum were elaborated in the present review. The information documented in this review was accessed using Google, Science Direct, Google Scholar and NCBI. Pharmacologically and medicinally important compounds are present within the S. nigrum, having great importance, predominantly steroidal compounds and many alkaloids. So far, around 188 phytoconstituents have been identified from S. nigrum. Among them, the major bioactive constituents are steroidal saponins, alkaloids, phenols, and polysaccharides. This review revealed different properties of S. nigrum of pharmaceutical value (cardioprotective, anti-ulcer, anti-microbial, antiviral, anticancer, anti-mycotoxin and nutritive importance) and their biological roles were elucidated. The current reviewed information will provide the therapeutic potential of S. nigrum. It will undoubtedly be helpful in developing new therapeutic and treatment options by discovering new drugs.